When Does Sexual Signal Exploitation Lead to Signal Loss? - Heinen-Kay, Justa L.; Zuk, Marlene (Frontiers in Ecology and Evolution, 2019)
Evolutionary loss of traits is common over evolutionary time and occurs in diverse taxa. Sexual signals and other non-signal traits should differ in their likelihood of becoming lost because they experience different selection pressures contributing to their diminution or persistence. In particular, conspicuous sexual signals are often exploited by natural enemies; this significant cost can favor signal reduction or loss. Yet sexual signals should also experience strong selection favoring their persistence because they facilitate communication during sexual encounters and their loss would involve changes in both the signaler and receiver. Most examples of sexual signal loss come from phylogenetic studies, so it is difficult to ascertain the context and key factors responsible for their loss. Here, we describe one of the best documented examples of evolutionary sexual signal loss in real time due to signal exploitation: Teleogryllus oceanicus (the Pacific field cricket) in Hawaii where many males have lost the ability to sing due to natural selection from a deadly, acoustically-orienting parasitoid fly. Using sexual signal loss in T. oceanicus as a model, we identify environmental, social, and genetic factors that appear generally important in driving sexual signal loss due to signal exploitation. We also discuss each putative factor contributing to signal loss more broadly within the context of non-signal trait loss. Overall, the factors that facilitate evolutionary loss of signals and other traits exhibit significant parallels. In general, a significant cost from the environment, weak selection for persistence, and alternative ways of accomplishing the former function appear critical to achieving evolutionary loss of both sexual signals and non-signal traits. However, because few empirical examples of sexual signal loss over contemporary timescales exist, we need more theory and empirical work to better understand the evolutionary dynamics of sexual signal loss.